The youngest South American rhynchocephalian, a survivor of the K/Pg extinction - Apesteguía, Sebastián (2014)
Rhynchocephalian lepidosaurs, though once widespread worldwide, are represented today only by the tuatara (Sphenodon) of New Zealand. After their apparent early Cretaceous extinction in Laurasia, they survived in southern continents. In South America, they are represented by different lineages of Late Cretaceous eupropalinal forms until their disappearance by the Cretaceous/Palaeogene (K/Pg) boundary. We describe here the only unambiguous Palaeogene rhynchocephalian from South America; this new taxon is a younger species of the otherwise Late Cretaceous genus Kawasphenodon. Phylogenetic analysis confirms the allocation of the genus to the clade Opisthodontia. The new form from the Palaeogene of Central Patagonia is much smaller than Kawasphenodon expectatus from the Late Cretaceous of Northern Patagonia. The new species shows that at least one group of rhynchocephalians not related to the extant Sphenodon survived in South America beyond the K/Pg extinction event. Furthermore, it adds to other trans-K/Pg ectotherm tetrapod taxa, suggesting that the end-Cretaceous extinction affected Patagonia more benignly than the Laurasian landmasses.